1989
DOI: 10.1093/ajcn/49.2.331
|View full text |Cite
|
Sign up to set email alerts
|

Resting metabolic rate in lean and obese children: relationship to child and parent weight and percent-overweight change

Abstract: Two studies were conducted to assess differences in metabolic rate as a function of child weight (study I); and the interaction of child and parent weight (study II). In both studies obese children had higher resting metabolic rates (RMRs) than lean children (p less than 0.05). Child weight accounted for 72 and 78% of the variance in RMR in studies 1 and 2, respectively. Including parental weight did not improve the prediction of RMR. After 6 mo of treatment, obese children decreased percent overweight, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
1
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
4
8
1
2
Order By: Relevance
“…Roughly equal numbers of studies have con®rmed and refuted a defect in food-induced thermogenesis in obese adults, 4,5,11 as well as in children 1,7,8,10,26 CIT was similar in our obese girls and in our controls, con®rming our previous report. 1 However, considerable interindividual variability in CIT values was seen in the obese patients, who fell into two groups, one with low and the other with normal CIT values.…”
Section: Discussionsupporting
confidence: 87%
“…Roughly equal numbers of studies have con®rmed and refuted a defect in food-induced thermogenesis in obese adults, 4,5,11 as well as in children 1,7,8,10,26 CIT was similar in our obese girls and in our controls, con®rming our previous report. 1 However, considerable interindividual variability in CIT values was seen in the obese patients, who fell into two groups, one with low and the other with normal CIT values.…”
Section: Discussionsupporting
confidence: 87%
“…Previous reports have demonstrated that absolute RMR is greater in obese children, but equal to that in lean individuals when expressed per kg of lean body mass or per unit surface area (7,8). Since there were no significant differences in FFM in the three groups of children by level of body fat in the present study, we did not expect any differences in RMR ~tween the groups.…”
Section: Discussioncontrasting
confidence: 40%
“…In the present study, FFM and FM were ϳ10.5 and 29 kg higher in obese compared with control subjects, respectively. Most previous studies found a significantly higher FFM in obese subjects (1,3,5,6,8,9), whereas in others, the FFM of obese and normal-weight subjects did not differ (2,4,7,10,11). This difference in FFM might explain the inconsistent absolute resting VO 2 among studies.…”
Section: Resting Vomentioning
confidence: 83%